Oceanic Lithosphere 4. The origin and evolution of oceanic lithosphere: Magmatic processes at oceanic spreading centres - Malpas, John; Robinson, Paul (Geoscience Canada, 2000)
Summary Primary melts generated in the oceanic mantle migrate upward and pond at major discontinuities to form magma chambers. Such chambers have thus far been identified only on fast- and intermediate-spreading ridges but probably also exist at slow-spreading ridges. The size, shape and longevity of subrift chambers reflect the magma supply rate, the extent of hydrothermal cooling, and the regional stress field. Ophiolite studies suggest small, ephemeral chambers rather than large, long-lived bodies. At fast-spreading ridges the chambers probably consist largely of crystalline mush, possibly with some melt sills, and a thin melt zone at the top. At slower-spreading ridges, magmatic activity is more episodic and seafloor spreading may be punctuated by periods of mainly tectonic extension. Fractionating melts inthe chambers are buffered by injections of more primitive melt from depth to produce the relatively uniform composition of MORB. The gross structural uniformity of the ocean crust must reflect extensive interplay and feedback of magmatic, hydrothermal and tectonic processes, resulting in a self-ordered system.